(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdcdGe aj eHGMK GdJYGOd hGdJQGLjM, (B... (3aEf GdJUhjH EfeG gh YHGQI Yf chf GdCMcGe OGFQI eOGQ GdXf Ch eOGQ GdYde HMjK jchf GdYde Ch GdXf JeGe GdehVhY HGdfSHI Edi GdMce hdh aj ehGQO GdNWCs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs